Serological and bacterial prevalence of Brucella spp. in suspected patients: a risk factor analysis in North Khorasan, Iran - Niloofar Sadooghi; Saeed Alamian; Hamed Ghasemzadeh Moghadam; Mohammad Yazdanmanesh; Maryam Dadar (Iranian Journal of Microbiology)
Background and Objectives: Brucellosis, a zoonotic bacterial disease caused by Brucella, affects humans and domestic animals, leading to significant economic loss. This study examined suspected cases in North Khorasan, Iran, to understand the prevalence of infection and its characteristics in this region. Materials and Methods: Blood specimens were collected from 200 patients suspected of brucellosis after obtaining informed consent. Serum samples were tested using RBPT, Wright, and 2-ME agglutination tests. Blood samples were cultured on Brucella agar, and positive cultures underwent biotyping and PCR assays. A questionnaire identified correlated risk factors. Results: RBPT, Wright, and 2-ME tests showed 25% brucellosis seroprevalence in symptomatic patients. In contrast, the prevalence was 2.5% among those with positive blood cultures. Notably, all culture-positive patients were also serologically positive, with titers exceeding 1:320 in Wright and 2-ME tests. Most positive cases were in people in their 30s, with B. melitensis biovar 1 identified as the causative agent, and the results were confirmed by multiplex PCR. Significant risk factors include contact with livestock and consumption of raw milk (P < 0.0001). Conclusion: The findings highlighted the importance of comprehensive diagnostic approaches for accurate identification of brucellosis. Furthermore, education regarding close contact with animals and pasteurization of dairy products is essential for controlling human brucellosis.